Condições de trabalho e de vida domiciliar dos assalariados da agropecuária da Região Sul - Nascimento, Carlos Alves do (Mundo Agrario.)
The article aims to measure the contingents of families of salaried workers in agriculture in the South region, and to analyze the working conditions and material home life of these workers. A typology of families and indices of work quality and living conditions were constructed based on microdata from the PNADs/IBGE from 2002 to 2014. The reference value for classifying the types of families was the minimum wage calculated by DIEESE. The period analyzed was one of considerable economic expansion and social development, in which the contingent of wage earners families who were in the worst social conditions was significantly reduced, but there was still a high participation of this number of wage earners in the sample analyzed in 2014.